Analysis of the conceptions of masculinity that give base to men interventions, as proposed by the public security plan of the Department of the Interior - Abarca Brown, Gabriel; Carvajal Fuentes, Carla; Cifuentes Astete, Ángela (Revista de Psicología, 2012)
This article analyzes the conceptions of masculinity thatground an intervention proposed by the Department of the Interior, which is addressed to men that commit violent acts against women who are their partners. This study is made through Masculinity(ies) Studies and contibutions of Queer Theory. Through Content Analysis, conceptions of normative and essentialist masculinity and hegemonichetero normativity of the sexes are revealed. The conceptions of the intervention show a superimposition of discourses that place it as a legal control tool, as well as a psychotherapeutic clinical space. Finally, other contributions of masculinity(ies) studies, that include semiotic definitions to the analysis, are highlighted.